TRANSURETHRAL REMOVAL FOR SUCCESSFUL DIAGNOSIS OF BLADDER MALAKOPLAKIA: A RARE CASE REPORT - Ivo Vujichikj (Sanamed, 2020)
Introduction: Malakoplakia is a rare granulomatous inflammatory disorder of infectious etiology that most often involves the urinary tract. Because it is so rare and can present in several different ways, malakoplakia poses a difficult diagnostic challenge.